A Comprehensive Review on Developed Pharmaceutical Analysis Methods by Iranian Analysts in 2018 - Elaheh Rahimpour; Sima Alvani-Alamdari; Abolghasem Jouyban (Tabriz University of Medical Sciences, 2020)
This article summarizes the publishing activities including bioanalytical and pharmaceutical analyses researches carried out in Iran in 2018 in order to connect academic researchers to those in industry, medical care units and hospitals. A wide spectrum of analytical methods has been used to determine and/or evaluate drug levels in the biological samples, based on physical, chemical and biochemical principles. We have compiled a concise survey of the literature covering 125 reports and tabulated the relevant analytical parameters. Chromatographic and electrochemical methods were found to be the technique of choice for many workers and almost 83% studies were performed by using these methods. This is the first annual review of the literature searching in SCOPUS database for published bioanalytical and pharmaceutical analysis researches in Iran.